Georgia Architectural and Historic Properties Survey of 520 West Ave., Valdosta, Ga., December 1980 - Smith, Bartholomew (South Georgia Area Planning and Development Commission, 1980)
Georgia Architectural and Historic Properties Survey of 520 West Ave., Valdosta, Ga., December 1980. Small, one story house of irregular plan with tin gabled roof. Shiplap siding. Interior chimney. Set on brick piers. Double hung sash windows with 2/2 lights. Poor condition. Date of Construction: Prior to 1922. Functional house in neighborhood probably settled by middle to low income families. Significant as part of a potential N.R. district running along the sides of West St.
Georgia Architectural and Historic Properties Survey of 520 West Ave., Valdosta, Ga., December 1980. 1 electronic record and assets. Digitized from originals. 1 PDF. 3 scans. 1 photograph. 2400 DPI TIF. 300 DPI 4x6 JPG. 78.8 MB (82,672,483 bytes).
Keywords: Historic buildings; Real property surveys; Lowndes County Historical Society (Lowndes County, Ga.); Valdosta (Ga.)